The Dialectical Interaction of Revelation and Culture in the Process of Forming Islamic Law - Ahmad Fauzan; Agus Iskandar; Muammar Syauqi (Al-Insan: Islamic and Humanities Perspectives Journal, 2025)
The central issue in this study is how revelation and culture interact dialectically in the formation of Islamic law, particularly when both possess the potential for conflict or convergence within social realities. The objective of this research is to uncover the concept of dialectical interaction between revelation and culture in shaping Islamic legal norms. The method employed is a qualitative phenomenological approach, focusing on the relationship between revelation and culture in the development of Islamic law. The data used in this study consists of relevant secondary literature sources. The findings reveal that the interaction between revelation and culture may take the form of assimilation, accommodation, or penetration, depending on the epistemological strength and the urgency of public interest (maṣlaḥah) involved. The study concludes that Islamic law is not static; rather, it remains open to cultural dynamics as long as they do not contradict the principles of maqāṣid al-syarī‘ah. The study recommends strengthening istinbāṭ methodologies that are responsive to local cultural contexts, as well as enhancing Islamic legal literacy that can wisely and sustainably bridge the values of revelation with social realities.